2018
DOI: 10.1101/500561
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Motivation and Cognitive Control in Depression

Abstract: Depression is linked to deficits in cognitive control and a host of other cognitive impairments arise as a consequence of these deficits. Despite of their important role in depression, there are no mechanistic models of cognitive control deficits in depression. In this paper we propose how these deficits can emerge from the interaction between motivational and cognitive processes. We review depression-related impairments in key components of motivation along with new cognitive neuroscience models that focus on… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 159 publications
(176 reference statements)
1
23
0
Order By: Relevance
“…It is proposed that individuals with greater depressive symptoms may lack the motivation necessary to engage in tasks (Phillips et al., 2013), and perhaps this impaired behavioural response results in blunted or lower CVR to psychological stress tasks. Furthermore others have found that motivation influences cognitive control (e.g., reduced rewards and anticipation of rewards); deficits in depression which may have relevance here (Grahek et al., 2019), as the effort to engage with the task will be attenuated in those who are depressed and not motivated. For example, studies have shown that depression is uniquely characterised by reduced enjoyment of approach based pursuits (Winch et al., 2015).…”
Section: Introductionmentioning
confidence: 82%
“…It is proposed that individuals with greater depressive symptoms may lack the motivation necessary to engage in tasks (Phillips et al., 2013), and perhaps this impaired behavioural response results in blunted or lower CVR to psychological stress tasks. Furthermore others have found that motivation influences cognitive control (e.g., reduced rewards and anticipation of rewards); deficits in depression which may have relevance here (Grahek et al., 2019), as the effort to engage with the task will be attenuated in those who are depressed and not motivated. For example, studies have shown that depression is uniquely characterised by reduced enjoyment of approach based pursuits (Winch et al., 2015).…”
Section: Introductionmentioning
confidence: 82%
“…Individual differences in expectations of efficacy may also play a significant role in determining one's motivation to engage in individual tasks or effortful behavior at large 19,21,[76][77][78] . Forms of amotivation, like apathy and anhedonia, are common across a variety of psychiatric and neurological disorders, and most likely reflect deficits in the process of evaluating potential incentive components; determining the overall EVC of candidate control signals; specifying the EVC-maximizing control allocation; and/or executing this control.…”
Section: Discussionmentioning
confidence: 99%
“…Another legitimate hypothesis would be that some of these patients with DDBS could be taking some antidepressant drugs associated with weight loss (e.g., fluoxetine). Furthermore, we suggest some reasons for the lower weight loss of patients with DDBS: the relationship between depression and binge eating behavior [24] or the lack of motivation that characterizes depression [25]. The signs and symptoms of depression should then be actively sought and in case of doubt or the clear presence of these, patients should be referred to a psychiatrist.…”
Section: Discussionmentioning
confidence: 99%